A high-performance TiO2 nanowire UV detector assembled by electrospinning. Issue 42 (16th May 2017) - Wang, Yuting; Cheng, Jing; Shahid, Muhammad; Zhang, Mengfei; Pan, Wei
Abstract : A transparent, flexible and high-performance TiO2 ultraviolet sensor has been fabricated by electrospinning. Abstract : Here, a transparent, flexible and nanoscale TiO2 ultraviolet (UV) photodetector has been fabricated by electrospinning. Well aligned TiO2 nanowires were collected on a flexible mica substrate. Then, the nano-device was simply assembled by depositing interdigitated platinum electrodes on the surface. Upon UV illumination, the photosensitivity of this device is up to over three orders of magnitude with relatively fast and stable response speed under 254 nm and 365 nm UV light. This nanosensor retains a high photo-dark current ratio, fast response time and stable durability during bending tests, indicating an excellent reversibility and stability of the flexible TiO2 nanowires. The highly flexible photosensor demonstrates a good potential candidate for wearable optoelectronic applications.